Effects of adding and removing dietary fat on growth performance and carcass characteristics of growing-finishing pigs - M De La Llata; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1999)
We conducted an experiment using 1,050 growing-finishing pigs to determine the carryover effect of adding and removing fat in diets. The experimental treatments consisted of six different sequence arrangements of diets without fat or with 60/0 added fat. Diets were fed in four phases. During each phase, ADFI and F/G were decreased when fat was added to the diets. Fat inclusion in the diet during one phase had no influence on the response to fat addition during another phase. Back-fat depth was increased and fat-free lean index decreased when fat was added to the diet during all phases, but not when fat was added to the diet during phases 1, 2, and/or 3.; Swine Day, Manhattan, KS, November 18, 1999
Keywords: Swine day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 841; Swine; Dietary fat; Subsequent performance; Finishing pigs